Structural and Electronic Transitions in Liquid FeO Under High Pressure. Issue 11 (5th November 2022) - Morard, Guillaume; Antonangeli, Daniele; Bouchet, Johann; Rivoldini, Attilio; Boccato, Silvia; Miozzi, Francesca; Boulard, Eglantine; Bureau, Hélène; Mezouar, Mohamed; Prescher, Clemens; Chariton, Stella; Greenberg, Eran
Abstract: FeO represents an important end‐member for planetary interiors mineralogy. However, its properties in the liquid state under high pressure are poorly constrained. Here, in situ high‐pressure and high‐temperature X‐ray diffraction experiments, ab initio simulations, and thermodynamic calculations are combined to study the local structure and density evolution of liquid FeO under extreme conditions. Our results highlight a strong shortening of the Fe‐Fe distance, particularly pronounced between ambient pressure and ∼40 GPa, possibly related with the insulator to metal transition occurring in solid FeO over a similar pressure range. Liquid density is smoothly evolving between 60 and 150 GPa from values calculated for magnetic liquid to those calculated for non‐magnetic liquid, compatibly with a continuous spin crossover in liquid FeO. The present findings support the potential decorrelation between insulator/metal transition and the high‐spin to low‐spin continuous transition, and relate the changes in the microscopic structure with macroscopic properties, such as the closure of the Fe‐FeO miscibility gap. Finally, these results are used to construct a parameterized thermal equation of state for liquid FeO providing densities up to pressure and temperature conditions expected at the Earth's core‐mantle boundary. Plain Language Summary: In the frame of the understanding of planetary differentiation processes, liquid FeO represents an important archetypal end‐member, as it is as important for the mantle side as well as for the core side. Combining in situ X‐ray diffraction under extreme pressure and temperature, with ab initio simulations and thermodynamic modeling, our study highlights the relation between electronic and structural properties in liquid FeO, as well as their implications for macroscopic features such as closure of the Fe‐FeO miscibility gap or the thermal equation of state of liquid FeO at Earth's core‐mantle boundary conditions. Key Points: Shortening of the Fe‐Fe bond length in liquid FeO is correlated with the insulator to metal transition in solid state Liquid FeO density smoothly evolves from high spin to low spin between 60 and over 150 GPa Changes in the microscopic structure are related to macroscopic properties, such as the closure of the Fe‐FeO miscibility gap